Ceftriaxone Associated Biliary Sludge in Children - A Study in Bangabandhu Sheikh Mujib Medical University (Bangladesh Journal of Child Health, 2014)
Background: Ceftriaxone is known to induce reversible precipitations, called billiary sludge or pseudolithiasis in the gall bladder.Objective: The aim of this study was to investigate the frequency of biliary sludge and factors that contribute to this side effect in children. Methodology: This study was conducted on 50 consecutive children who were admitted at paediatric department of Bangabandhu Sheikh Mujib Medical University (BSMMU) for different illness and who received ceftriaxone in different dosage and duration. Ultraso-nography of hepatobiliary system was done before and at the end of therapy. Children who developed biliary sludge, a third ultrasonography was done after one month. Results: Biliary sludge was found in 4 (08%) of 50 children which resolved within 30 days of cessation of therapy. The mean dose and duration of ceftriaxone in these four children were 92.5±9.6 mg/kg/day and 8.0±2.0 days respectively while it was 78.5±5.2 mg/kg/day and 6.1±1.2 days respectively rest 46 children who did not develop biliary sludge (p